1988
DOI: 10.1038/hdy.1988.28
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of populations of sexual and asexual Taraxacum (dandelions)

Abstract: The genetic structure, as assessed by isozymes, is described for three populations of outbreeding sexuals, three populations of obligate agamosperms, and six accessions of inbreeding sexual Taraxacum. Fifteen loci in 10 isozyme systems were identified, and isozyme bands were previously shown to be allelic in sexual x sexual and were confirmed as allelic in sexual x agamosperm crosses. Sexual x agamosperm crosses gave rise to both diploid sexual and tetraploid agamospermous offspring. Eight loci were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 19 publications
4
36
0
1
Order By: Relevance
“…This report also showed that in two cases at least one facultative agamospermous plant occurred in progenies but all other progeny were sexuals. More recently, Muller (1972), Jenniskens (19846) and Hughes & Richards (1988) using Ruderalia plants, have reported further investigations. In Muller (1972), 260 progeny plants of 2x-3x crosses were sexual diploids and only nine progeny plants were triploid facultative agamosperms.…”
Section: X~3x Crosses and The Diploid-triploid Cyclementioning
confidence: 99%
See 3 more Smart Citations
“…This report also showed that in two cases at least one facultative agamospermous plant occurred in progenies but all other progeny were sexuals. More recently, Muller (1972), Jenniskens (19846) and Hughes & Richards (1988) using Ruderalia plants, have reported further investigations. In Muller (1972), 260 progeny plants of 2x-3x crosses were sexual diploids and only nine progeny plants were triploid facultative agamosperms.…”
Section: X~3x Crosses and The Diploid-triploid Cyclementioning
confidence: 99%
“…Recently Hughes and Richards (1988) concluded from electrophoretic analysis that diploid progeny from crosses beween a diploid microspecies of section Ruderalia and the triploid T. pseudohamatum were indeed hybrids. T. pseudohamatum Dahlst.…”
Section: X~3x Crosses and The Diploid-triploid Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…A population sample may comprise, randomly sampled apomictic dandelions (eg Lyman and Ellstrand, 1984;Menken et al, 1995;Van der Hulst et al, 2000). Alternatively, a population sample may correspond to a set of apomicts, selected on the basis of certain morphological features that are diagnostic for microspecies (eg Hughes and Richards, 1988;. As our aim was to analyse genetic variation in a stand of apomicts and to infer whether apomicts have clonal relationships, we applied the first type of sampling.…”
Section: General Interpretationmentioning
confidence: 99%